1998
DOI: 10.1103/physrevd.58.096013
|View full text |Cite
|
Sign up to set email alerts
|

DirectCPviolation inΛbn(Λ)π+

Abstract: We study direct CP violation in the bottom baryon decays Λ b → f ρ 0 (ω) → f π + π − (f = n or Λ). It is found that in these decays via ρ − ω mixing the CP violation could be very large when the invariant mass of the π + π − pair is in the vicinity of the ω resonance. With a typical value N c = 2 in the factorization approach, the maximum CP-violating asymmetries are more than 50% and 68% for Λ b → nπ + π − and Λ b → Λπ + π − , respectively.With the aid of heavy quark symmetry and phenomenological models for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…As a consequence the physical ρ 0 and ω mesons are not eigenstates of isospin but, for example, the physical ρ 0 contains a small admixture of an I = 0 state [13]. In previous works, this phenomenon, known as ρ-ω mixing, was considered to obtain a large strong phase in B decays [14][15][16][17] and it was found that such a mixing can lead to a peak of CP violation when the invariant mass of π + π − is near ω. The differential CP asymmetry was studied in the decays B ± → ρ 0 (ω)π ± → π + π − π ± before [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence the physical ρ 0 and ω mesons are not eigenstates of isospin but, for example, the physical ρ 0 contains a small admixture of an I = 0 state [13]. In previous works, this phenomenon, known as ρ-ω mixing, was considered to obtain a large strong phase in B decays [14][15][16][17] and it was found that such a mixing can lead to a peak of CP violation when the invariant mass of π + π − is near ω. The differential CP asymmetry was studied in the decays B ± → ρ 0 (ω)π ± → π + π − π ± before [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…(15) that both weak and strong phase differences are responsible for CP violation. ρ-ω mixing introduces the strong phase difference and is well known for the three-body decay processes of the bottom hadron [28][29][30][31][32][33][34]. Due to ρ-ω interference from u and d quark mixing, we can write the formalism in an approximate form in terms of the first order isospin violation:…”
Section: The Effective Hamiltonianmentioning
confidence: 99%
“…(17) and (18) compared with the case of single ρ-ω interference [28][29][30][31][32][33][34][35][36]. From Eqs.…”
Section: The Effective Hamiltonianmentioning
confidence: 99%
“…ρ-ω mixing has the dual advantages that the strong phase difference is large and well known [24,25]. From a series of studies on CP violation, it has already been found that this mechanism can provide a very large strong phase difference (usually 90 degrees) when the mass of the decay product of ρ 0 (ω) , π + π − , is in the vicinity of the ω resonance in some decay channels of heavy hadrons including B, b , and D [24][25][26][27][28][29]. We will apply this mechanism to the τ lepton decay in the present paper.…”
Section: Introductionmentioning
confidence: 99%